América Latina nos livros didáticos do ensino médio: uma análise sob a perspectiva da Geografia Política - Martins, Claudio Roberto Ribeiro (2016)
This work aims to contribute to discussions about the present and the diversity of geopolitical approaches. We intend to identify and analyze the importance of geopolitics to the Geographic Science in the context of political and social changes occurring in the twenty-first century with the specific focus on Latin America. Through the theoretical study we will discuss the conceptual changes and the main references for the construction of Geopolitics and Political Geography for the geographical science. From there, we will discuss the contribution of concepts such as territory and politics within the geography and the validity of new social actors in building the Critical Geopolitics. The theoretical basis helped to read and understanding of geopolitics in Latin America, its territorial and political issues and its representation in the textbook of geography high school of the state of São Paulo